Unusual Cysteine Content in V1 Region of gp120 From an Elite Suppressor That Produces Broadly Neutralizing Antibodies - Hutchinson, Jennie M.; Mesa, Kathryn A.; Alexander, David L.; Yu, Bin; O'Rourke, Sara M.; Limoli, Kay L.; Wrin, Terri; Deeks, Steven G.; Berman, Phillip W. (Frontiers in Immunology, 2019)
Although it is now possible to produce recombinant HIV envelope glycoproteins (Envs) with epitopes recognized by the 5-6 major classes of broadly neutralizing antibodies (bNAbs), these have failed to consistently stimulate the formation of bNAbs in immunized animals or humans. In an effort to identify new immunogens better able to elicit bNAbs, we are studying Envs derived from rare individuals who possess bNAbs and are able to control their infection without the need for anti-retroviral drugs (elite supressors or ES), hypothesizing that in at least some people the antibodies may mediate durable virus control. Because virus evolution in people with the ES only phenotype was reported to be limited, we reasoned the Env proteins recovered from these individuals may more closely resemble the Envs that gave rise to bNAbs compared to the highly diverse viruses isolated from normal progressors. Using a phenotypic assay, we screened twenty-five controllers and identified two for more detailed investigation. In this study, we examined 20 clade B proviral sequences isolated from an African American woman, who had the rare bNAb/ES phenotype. Phylogenetic analysis of proviral envelope sequences demonstrated low genetic diversity. Envelope proteins were unusual in that most possessed two extra cysteines within an elongated V1 region. In this report, we examine the impact of the extra cysteines on the binding to bNAbs, virus infectivity, and sensitivity to neutralization. These data suggest structural motifs in V1 can affect infectivity, and that rare viruses may be prevented from developing escape.